2016
DOI: 10.1016/j.athoracsur.2016.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postoperative Oral Nutrition Following Esophagectomy: A Multicenter Clinical Trial

Abstract: Immediate start of oral nutrition following esophagectomy seems to be feasible and does not increase complications compared to a retrospective cohort and literature. However, if complications arise an alternative nutritional route is required. This explorative study shows that a randomized controlled trial is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 38 publications
2
62
1
7
Order By: Relevance
“…As such, they reflect neither the typical Western esophageal cancer patient nor the cohort studied by Weijs et al (14). Their current study differs from other prior investigations in that the majority of their patients had locally advanced esophageal adenocarcinoma and underwent neoadjuvant chemoradiotherapy instead of proceeding directly to resection.…”
Section: Editorialcontrasting
confidence: 46%
“…As such, they reflect neither the typical Western esophageal cancer patient nor the cohort studied by Weijs et al (14). Their current study differs from other prior investigations in that the majority of their patients had locally advanced esophageal adenocarcinoma and underwent neoadjuvant chemoradiotherapy instead of proceeding directly to resection.…”
Section: Editorialcontrasting
confidence: 46%
“…On the contrary, the only two nonrandomized studies investigating early oral feeding following esophagectomy concluded that early oral feeding is feasible, safe, and does not increase complications [85,86], and is associated with a reduced length of hospital stay [85], compared to a nil-bymouth regime and tube feeding during the first week. A randomized controlled trial on the safety and feasibility of early oral feeding is ongoing [87].…”
Section: Initiation Of Nutritionmentioning
confidence: 99%
“…However, following esophagectomy early initiation of oral intake is believed to increase sequelae of anastomotic leakage and pneumonia rates. Though a safety and feasibility trial has shown encouraging results the results of a randomized controlled trial on this topic have to be awaited (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%